(untitled) (Research, Society and Development, 2024)
The teaching of Chemistry proves to be fundamental for everyday life in general. Therefore, Chemistry allows for offering a comprehensive and contextualized view of the world, enabling the connection of information from various sources and the analysis of interdisciplinary problems. Thus, it is acknowledged that the interdisciplinary approach in teaching Chemistry enriches education, shaping informed and well-rounded citizens to face challenges. In this context, this literature review aimed to explore the responsibility of Chemistry teaching, as well as its effectiveness in interdisciplinary approach regarding its impact on personal development. It was observed from this study that the interdisciplinary approach in teaching Chemistry emerges as an essential pedagogical strategy to meet the increasing demands for a more relevant and comprehensive education. Furthermore, Chemistry demonstrates its value as a fundamental tool by integrating with other disciplines, for the understanding of the natural world and its relation to social, economic, and environmental aspects.